2017
DOI: 10.1186/s12891-017-1728-5
|View full text |Cite
|
Sign up to set email alerts
|

Total knee Arthroplasty: risk factors for allogeneic blood transfusions in the South Asian population

Abstract: BackgroundTotal knee arthroplasty (TKA) is the recommended treatment for end-stage knee osteoarthritis. Considering the various risks associated with intra and postoperative blood transfusions, better understanding is required with respect to the risk factors contributing to a greater possibility of blood transfusion during or after surgery. Although literature highlights several such factors, our study is among the first to identify these risk factors in the South Asian population which differs from other pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Compared with those undergoing unilateral TKA, patients undergoing simultaneous bilateral TKA have a higher risk of transfusion. Similar results have been described in previous studies, and longer operation times and more perioperative blood loss may be the reason behind this result [18][19][20]. Our study suggested that patients with lower BMIs had a higher risk of transfusion.…”
Section: Discussionsupporting
confidence: 91%
“…Compared with those undergoing unilateral TKA, patients undergoing simultaneous bilateral TKA have a higher risk of transfusion. Similar results have been described in previous studies, and longer operation times and more perioperative blood loss may be the reason behind this result [18][19][20]. Our study suggested that patients with lower BMIs had a higher risk of transfusion.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, low preoperative Hb, CCF, ASA-PS (3), and GA were significantly independent risks for blood transfusion in TKA, which is consistent with the results of recently published studies. [20][21][22][23] However, none of them discussed the association between choice of anesthesia and the risk of blood transfusion events.…”
Section: Discussionmentioning
confidence: 99%
“…The Hb level criterion used for transfusion is decreasing. In our study, the criterion for blood transfusion was strictly limited to cases with a Hb level <7 g/dL [ 15 , 16 , 17 ]. However, a Hb threshold of 8 g/dL was applied to patients with cardiovascular disease [ 18 ].…”
Section: Methodsmentioning
confidence: 99%